3D nanosheet networks like mesoporous structure of NiO/CoSe2nanohybrid directly grown on nickel foam for oxygen evolution process. Issue 1 (31st December 2022) - Ghafoor Abid, Abdul; Al Huwayz, Maryam; Alwadai, Norah; Manzoor, Sumaira; Munawar, Tauseef; Iqbal, Faisal; Hua, Ruimao; Aman, Salma; Al-Buriahi, M. S.; Naeem Ashiq, Muhammad
Abstract : The advancement of energy conversion and storage frameworks depends significantly on the development of reliable, effective, and affordable electrocatalysts. Steadily, there is an increasing demand of energy, fossil fuels consumption, and alarming environmental issues that have induced researchers to find alternate renewable sources. For this purpose, water splitting using various electrocatalysts have been investigated in a highly favourable virtual environment and is a highly demanding challenge to fulfil the energy crises. Here in this work, we fabricated three-dimensional (3D) nanosheet network NiO/CoSe2 /NF nanocomposite (where NF represents nickel foam) material via hydrothermal treatment. All the synthesized materials like NiO/NF, CoSe2 /NF, and NiO/CoSe2 /NF nanohybrid are tested for the oxygen evolution process in a basic medium (1.0M KOH). Among all directly grown NiO/CoSe2 3D nanosheet has shown the lowest overpotential (263 mV), Tafel slope value (38 mVdec −1 ), which is remarkably improved as compared to the pristine NiO/NF and CoSe2 . The resultant enhanced performance is due to improved morphological characteristics, increased surface area, and electrochemical coupling of electrons between NiO/NF and CoSe2 /NF due to the synergistic effect.